CONTEMPORARY LEGAL HERMENEUTICS: A CRITIQUE OF TRADITIONAL METHODS OF INTERPRETING THE LAW - Жоровля, Эльвира; Codreanu, Alina (SWorldJournal, 2026)
The historical evolution of interpretive techniques in legal hermeneutics reveals a rich and dynamic tradition, shaped by the complexities of law throughout the centuries. Early legal interpretation drew inspiration from classical philosophy and religious